Seven One-Act Plays by Holberg - Holberg, Ludvig; Alexander, Henry (Princeton, NJ : Princeton University Press, 2015)
These short plays by the great Danish-Norwegian playwright Ludvig Holberg reveal, in brilliant and sparking miniature, his genius for comedy. The plays are here translated into English for the first time, with an introduction by Svend Kragh-Jacobsen, well-known Danish theater critic. In these social comedies Holberg pricks the vanity of snobbery and the worship of riches, deals with the world of the philosophers, and has fun with the theme of common sense. A talkative barber, a scientific charlatan, and an ignorant farmer boy come in for sharp characterization.Originally published in 1950.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- CONTENTS -- Introduction / Kragh-Jacobsen, Svend -- The Talkative Barber (7722) -- The Arabian Powder (1724) -- The Christmas Tarty (1724) -- Diderich the Terrible (1724) -- The Peasant in Pawn (1726) -- Sganarel's Journey to the Land of the Philosophers (1751) -- The Changed Bridegroom (1753) -- Backmatter
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Danish drama; LITERARY CRITICISM / Drama